Dampak Covid-19 Bagi Para Pihak Dalam Perjanjian E-Commerce - Monalesya Dince Sapulette; Agustina Balik (Faculty of Law, Universitas Pattimura, 2023)
Introduction: One of the most important consumer rights is the right to comfort and safety in consuming goods and/or services. The emergence of the Covid-19 pandemic has become a challenge for consumers, both in consuming goods for their daily needs and services through e-commerce sales and purchase agreements. Therefore, the right of consumers to comfort and safety in consuming goods and/or services is based on Article 4 of Law No. 8 of 1999 concerning consumer protection during the Covid-19 pandemic.Purposes of the Research: This study aims to find out how consumer legal protection is during the Covid-19 pandemic and how the impact of Covid-19 on the parties in e-commerce agreements.Methods of the Research: In writing this thesis the author uses normative research methods, uses a factual approach and statutory approach. Normative legal research is also known as doctrinal legal research, and is then analyzed qualitatively descriptively in order to produce a conclusion.Results of the Research: Based on the research results obtained, that consumer protection is all efforts made to protect the interests and ensure legal certainty for consumers. In this effort, the rights and obligations of consumers and business actors cannot be separated. The Covid-19 pandemic has had a major impact on consumers' rights to comfort and safety in consuming goods and/or services in e-commerce agreements. Therefore, legal protection for consumers is needed both preventively and repressively so that every consumer's rights can be protected and their rights are maintained.